Factors affecting graft infection after cranioplasty in department of neurosurgery Hospital Kuala Lumpur - Mohammad, Siti Azleen (2014)

(untitled)
Background: Cranioplasty, one of the oldest surgical procedure used for cranial defect repair. It has undergone many evolution over time to find ideal technique and material to improve patient’s prognosis. The most common complication post cranioplasty is graft infection. It may poses substantial burden of disease for both patients and healthcare services in terms of morbidity, mortality and economic cost. Therefore this study is to determine factors affecting graft infection after cranioplasty procedure. Objectives: This study was done to determine incidence of graft infection after cranioplasty procedures in Hospital Kuala Lumpur in 2012 and factors affecting graft infection rate. Methodology: Observational cross-sectional case study on the patients who have undergone cranioplasty procedure at Hospital Kuala Lumpur (HKL) over period of 1 year (2012). Identified 172 patients included in the study. A total of 105 (61.8%) cases were autologous bone and 67 (38.2%) were acrylic cranioplasty. Patients’ case notes were reviewed and relevant demographic, clinical, surgical treatment documented. Graft infection is defined according to the Center for Disease Control and Prevention definitions. Statistic analysis if Fisher exact and Pearson chi-square test were used to determine factors associated with outcome. Result: A total of 5 infected graft have been identified among 172 cases included in the study, resulting in an overall infection rate of 2.9%, within this infection rate involving acrylic is 3 (4.5%) and 2(1.9%) in autologous bone. There was high proportion of male patients undergoing cranioplasty, 118 (or 68.6%) where female were 54 (or 31.4%). Primary pathology in majority of patients was due to trauma seen in 126 (or 73.2%) where non trauma contribute to 46 cases (or 26.8%). Patients undergone a single cranial procedure prior to cranioplasty were 123 (or 71.5%) and whereas the balance 43 (or 28.5%) patients underwent multiple cranial procedures. Majority of the patients underwent cranioplasty 90 days after decompressive craniectomy were performed, 114 (or 66.3%) and 58 (or 33.7%) had cranioplasty before 90 days. Patients that undergone cranioplasty mostly have GCS more than 8, 137 (or 79.7%) and GCS less than 8 were 35 (or 20.3%). The prevalence (proportion) of infection rate between group bone and acrylic are not significantly different (P = 0.379). Therefore, there is no significant association between these group and infection rate. The prevalence of infection rate between gender showed no significant different as well where P = 0.327 (P<0.05). Thus, we have no significant evidence to conclude that the association between gender and infection rate exist. While testing for association between infection rate and other variables under interest individually, which is mechanism of injury, number of procedure, timing, and GCS; the proportion of infection rate between those variables are not significantly different where the P value are 0.326; P = 0.140; P = 0.664; and P = 0.585 respectively. All this P-value are more than 0.05, thus the association between these variables and infection rate are not significant. Conclusion: Cranioplasty is a surgical procedure for anatomical reconstruction, brain protection and cosmetics. Infection rate overall for cranioplasty is relatively low, 2.9%. When comparing infection rate of graft material, gender, primary pathology, number of procedures, time interval, and GCS pre cranioplasty, no significant difference noted.